Chiral symmetry restoration in strange hadronic matter; Physical Review C; Vol. 70, iss. 1 - Wang P.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Gutsche Th.; Faessler A. (2004, 2004)
Title screen